2021
DOI: 10.1016/j.vgie.2021.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Underwater endoscopic mucosal resection of a rectal adenoma in the nondistensible rectum from severe fecal incontinence

Abstract: Video Video 1 Underwater endoscopic mucosal resection of a rectal adenoma in nondistensible rectum from severe fecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…One case report described UEMR for rectal adenoma in the non‐distensible rectum arising from severe fecal incontinence, 57 and indicated that UEMR can even be successful in situations where the performance of CEMR and ESD is difficult. However, some endoscopists remained skeptical about UEMR as a special procedure and investigated techniques to decrease the difficulty of UEMR in case reports that utilized peristalsis, 58 a snaring technique, 59 and a special device 60 .…”
Section: Uemr In Case Reports Under Special Situationsmentioning
confidence: 99%
“…One case report described UEMR for rectal adenoma in the non‐distensible rectum arising from severe fecal incontinence, 57 and indicated that UEMR can even be successful in situations where the performance of CEMR and ESD is difficult. However, some endoscopists remained skeptical about UEMR as a special procedure and investigated techniques to decrease the difficulty of UEMR in case reports that utilized peristalsis, 58 a snaring technique, 59 and a special device 60 .…”
Section: Uemr In Case Reports Under Special Situationsmentioning
confidence: 99%